Regulasi emosi dan resiliensi pada dewasa madya dalam Generasi Sandwich - Azzahra, Tisya Meutia; Qarni, Waizul (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
This study aims to see the contribution of emotional regulation and resilience experienced by middle-aged adults as a sandwich generation who care for parents and children. The condition as a sandwich generation generally feels physically, mentally, and financially exhausted because they often face challenges and pressures as caregivers. In the same situation, this individual must also balance the demands of his own family, including raising children, with the responsibility of providing physical, emotional, and financial support to his elderly parents. This study uses a quantitative method. The population involved were middle-aged adults who were sandwich generation in Perawang Barat Village, Tualang District using convenience sampling techniques, participants consisting of 54 respondents. The measuring instrument used was the Emotional Regulation Questionnaire (ERQ) from Radde et al. (2021) which is based on the dimensions of Gross & John (2003). Meanwhile, the resilience scale uses a theory based on Grotberg's aspects. The results of the study showed that the level of emotional regulation and resilience of middle-aged adults in the sandwich generation in Perawang Barat Village was at a moderate level. In addition, there is a positive and significant relationship between emotional regulation and resilience. The findings of this study can be used by individuals, parents, and psychologists to improve their ability to regulate emotions, so that they are resilient in facing problems as a sandwich generation.